Noncognitive Abilities and Within-Group Wage Inequality - Hartmut Egger; Volker Grossmann (Institute for the Study of Labor (IZA), 2004)
This paper argues that endogenous restructuring processes within firms towards productivityenhancing human resource activities, triggered by advances in information and communication technologies (ICT) and rising supply of educated workers, are typically associated with higher demand for noncognitive abilities. Consistent with the evolution of the distribution of wages in advanced countries, this raises within-group wage inequality, possibly accompanied by a decline or stagnation of between-group wage dispersion. The mechanisms proposed in this research are consistent with empirical evidence on both the evolution of work-force composition in firms and the complementarity between skillupgrading, new technologies and knowledge-based work organization.
Keywords: J31; D20; 330; human resource activities; noncognitive abilities; within-group wage inequality; Lohnstruktur; Bildungsinvestition; Kognition; Informationstechnik; Computergestütztes Verfahren; Theorie